INTERVENTION OF ACTOR INTERACTION PATTERNS ON TRANSBOUNDARY FLOOD RISK MANAGEMENT RELATED PREVENTION AND STRUCTURAL MITIGATION EFFORTS IN THE CILIWUNG RIVER BASIN - Ganesha, Deliyanti
Prevention and structural mitigation efforts in transboundary flood risk management in the Ciliwung river basin have not been fully implemented optimally due to issues and constraints on land acquisition, sectoral egos and overlapping policies in the distribution of authority between related actors. This study aims to formulate recommendation for the interventions of actor interaction patterns in transboundary flood risk management in the Ciliwung river basin, especially in prevention and structural mitigation activities. Data collection methods consist of primary and secondary data. The secondary data comes from government documents, journals, theses and academic books. Then, the primary data was obtained through online and offline interviews with 34 government agencies consisting of the central government, DKI Jakarta Provincial Government, Depok and Bogor City Governments and Bogor Regency Government to the smallest units that is sub districts and villages. The analysof the study conducted content analysis, Social Network Analysis (SNA) using UCINET software and descriptive analysis. Based on the results of the analysis, it is known that there are 15 activity components in the prevention and structural mitigation of flood disasters in the Ciliwung river basin which consists of two activities in the Resist strategy, namely the construction of sea dikes and polder systems, two activities in the Delay strategy, namely Naturalization of Rivers and Reservoirs and construction of infiltration wells, three activities in the Store strategy, namely the construction of Ciawi and Sukamahi Dry Reservoirs, Situ, Embung, Reservoirs and Retention Ponds. Eight other activities in the Discharge strategy are Normalization of Ciliwung River, Drainage of Ciliwung River to BKT, Normalization of BKB and BKT, Construction and Normalization of Drainage/Channels, Construction and Maintenance of Pumps, Construction and Maintenance of Water Gate, Widening and Deepening of River Estuaries and Construction of Garbage Filters. There are 52 actors involved in the 15 components of the activities with different interaction patterns. The actors involved consist of 9 actors of Central Government, 12 actors of DKI Jakarta Provincial Government actors, 4 actors of West Java Provincialiv Government, 8 actors of Depok City Government, 8 actors of Bogor City Government and 8 actors of Bogor Regency Government actors, BUMN actors and Private actors as well as individual community actors. The interaction patterns of actors are obtained by using a degree of centrality and betweenness indicators so that it is known the way of interaction of each activity with their respective characters. The results of the analysis showed that there were diverse interaction patterns. There are six components of activities dominated by the central government namely Balai Besar Sungai Ciliwung Cisadane (BBWS CC) and one component of activities dominated by the Ministry of PUPR. In addition, there are six components of activities dominated by the local government, namely five component of activities dominated by the Water Resources Office (DSDA) of DKI Jakarta Province and one activity by the Environment Office (DLH) of DKI Jakarta Province. There are also two component of activities dominated by BBWS CC and DSDA of DKI Jakarta Province (mix collaboration). . In the interaction pattern of these actors, there are issues and constraints related to coordination. The most diverse issues and constraints are found in the activity component which is dominated by Central Government actors. There are 5 issues and constraints that often occur in activities dominated by the central government. The first issue is related to land acquisition which can be intervened by improving intensive coordination between land acquisition actors and affirming the implementation of PP no. 19 of 2021 regarding procedures for land acquisition. The second constrain is the limited budget that can be intervened by utilizing other funding systems such as PEN, CSR and grants. The third constrain, namely the lack of community involvement in the initial planning,which can be intervened by involving community actors in preparing the Initial Activity Plan. Meanwhile, the fourth constraint related to the different levels of authority can be intervened by simplifying the coordination mechanism in licensing and preparing technical recommendations. The last constraint related to the lack of coordination between the central and local governments can be intervened by improving coordination between central, provincial and city/district government actors.